Adapting to the Cold: A Role for Endogenous Fibroblast Growth Factor 21 in Thermoregulation? - Klein Hazebroek, Marlou; Keipert, Susanne (Frontiers in Endocrinology, 2020)
Fibroblast growth factor 21 (FGF21) is in the biomedical focus as treatment option for metabolic disease, given that administration improves metabolism in mice and humans. The metabolic effects of exogenous FGF21 administration are well characterized, but the physiological role of endogenous FGF21 has not been fully understood yet. Despite cold-induced FGF21 expression and increased circulating levels in some studies, which co-occur with brown fat thermogenesis, recent studies in cold-acclimated mice demonstrate dispensability of FGF21 for maintenance of body temperature, thereby questioning FGF21’s role for thermogenesis. Here, we discuss the evidence either supporting or opposing the role of endogenous FGF21 for thermogenesis based on the current literature. FGF21 secreted by brown fat or liver is likely not required for energy homeostasis in the cold, but the nutritional conditions could modulate the interaction between FGF21, energy metabolism and thermoregulation.